2021
DOI: 10.1093/tropej/fmab047
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Feeding Practices and Sociodemographic Factors on Underweight and Wasting in Children in Ethiopia: A Secondary Analysis of Four Health Surveys from 2000 to 2016

Abstract: Background Feeding practices highly influence the nutritional status of children between 6 and 23 months of age in developing countries, including Ethiopia. Therefore, this study was conducted to investigate the association of feeding practices and sociodemographic factors on underweight and wasting of children aged 6–23 months in Ethiopia. Methods Data on 8003 children 6–23 months of age from four Ethiopia demographic and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…In our study Maternal dietary intake was inadequate given that around half (47.1%) of the mothers attained the practice of minimum dietary diversity (MDD) during the antenatal period. contrary to the other studies reveals that MDD-W was low, indicating a low-quality diet, with 34% acceptable maternal diet variety (3,5,7,8,9) . During each trimester of the antenatal period, mothers were asked to list the foods they ate on a regular basis.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study Maternal dietary intake was inadequate given that around half (47.1%) of the mothers attained the practice of minimum dietary diversity (MDD) during the antenatal period. contrary to the other studies reveals that MDD-W was low, indicating a low-quality diet, with 34% acceptable maternal diet variety (3,5,7,8,9) . During each trimester of the antenatal period, mothers were asked to list the foods they ate on a regular basis.…”
Section: Discussioncontrasting
confidence: 78%
“…Approximately half of studies from Asia (6/11) (Ahmed et al, 2012 ; Fuada et al, 2020 ; Hossain et al, 2020 ; Mashal et al, 2008 ; Ngoc Hien & Ngoc Hoa, 2009 ; Nguyen et al, 2017 ) indicated an increased risk of moderate underweight for children born to adolescent versus adult mothers, compared to two‐thirds of studies from SSA (8/12) (Boah et al, 2019 ; Friebert et al, 2017 ; Gbadamosi et al, 2017 ; Hiruy et al, 2021 ; Ickes et al, 2015 ; Linnemayr et al, 2008 ; Poda et al, 2017 ; Sobkoviak et al, 2012 ). No comparison by setting was possible for severe underweight, due to the limited number of studies included in the qualitative synthesis for this outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (15/24, 63%) which reported data for moderate underweight (Supporting Information: Appendix 5a ) indicated an increased risk for children born to adolescent compared to adult mothers (Ahmed et al, 2012 ; Boah et al, 2019 ; Friebert et al, 2017 ; Fuada et al, 2020 ; Gbadamosi et al, 2017 ; Hiruy et al, 2021 ; Hossain et al, 2020 ; Ickes et al, 2015 ; Linnemayr et al, 2008 ; Mashal et al, 2008 ; Ngoc Hien & Ngoc Hoa, 2009 ; Nguyen et al, 2017 ; Poda et al, 2017 ; Schott et al, 2017 ; Sobkoviak et al, 2012 ). A total of three studies (13%) indicated a reduced risk of underweight for children born to adolescent mothers (Ali et al, 2019 ; Nakamori et al, 2010 ) and four (17%) indicated no difference (Akseer et al, 2018 ; Bekele et al, 2021 ; Hien & Kam, 2008 ; Kasaye et al, 2019 ; Kumar & Paswan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (15/24, 63%) which reported data for moderate underweight (Supplementary Appendix 5b) indicated an increased risk for children born to adolescent compared to adult mothers (Ahmed et al, 2012;Boah, Azupogo, Amporfro, & Abada, 2019;Friebert, Callaghan-Gillespie, Papathakis, & Manary, 2017;Fuada, Latifah, Yunitawat, & Ashar, 2020;Gbadamosi, Goon, & Tugli, 2017;Hien & Hoa, 2009;Hiruy et al, 2021;Hossain et al, 2020;Ickes, Hurst, & Flax, 2015;Linnemayr, Alderman, & Ka, 2008;Mashal et al, 2008;Nguyen et al, 2017;Poda, Hsu, & Chao, 2017;Schott, Aurino, Penny, & Behrman, 2017;Sobkoviak, Yount, & Halim, 2012). A total of three studies (13%) indicated a reduced risk of underweight for children born to adolescent mothers (Ali et al, 2019;Nakamori et al, 2010) and four (17%) indicated no difference (Akseer et al, 2018;Bekele, Rawstorne, & Rahman, 2021;Hien & Kam, 2008;Kasaye, Bobo, Yilma, & Woldie, 2019;Kumar & Paswan, 2021).…”
Section: Child Underweightmentioning
confidence: 99%
“…Approximately half of studies from Asia (6/11) (Ahmed et al, 2012;Fuada et al, 2020;Hien & Hoa, 2009;Hossain et al, 2020;Mashal et al, 2008;Nguyen et al, 2017) indicated an increased risk of moderate underweight for children born to adolescent versus adult mothers, compared to two thirds of studies from SSA (8/12) (Boah et al, 2019;Friebert et al, 2017;Gbadamosi et al, 2017;Hiruy et al, 2021;Ickes et al, 2015;Linnemayr et al, 2008;Poda et al, 2017;Sobkoviak et al, 2012). Like severe wasting, a lack of data prevented geographical comparison for severe underweight.…”
Section: Outcomes By Geographic Locationmentioning
confidence: 99%